(untitled) (Comunicação & Inovação, 2024)
This proposal aims to reflect on the relationship between communication and development in the Centro Criativo-Gare de Santa Maria-RS region, in addition to understanding how cultural movements are linked to development policies through communication and innovation. From the research we observed that the Creative District represents an alternative for urban planning in a more participatory and integrated way, seeks to protect local cultural heritage and seeks to universalize access to public spaces in a safe, inclusive and accessible way, revitalizing the places that mark the cultural identity of Santa Maria.